1980
DOI: 10.1136/thx.35.9.653
|View full text |Cite
|
Sign up to set email alerts
|

Hard metal lung disease: importance of cobalt in coolants.

Abstract: Four patients were found to react to occupational exposure to grinding of hard metal (tungsten carbide). Three of the patients had symptoms and signs compatible with an allergic alveolitis, the symptoms disappearing and the chest radiograph clearing when they were absent from work for a few months. Re-exposure to the offending agent led to new signs and symptoms. The first patient was re-exposed twice and each time reacted a little more seriously. After the last episode her chest radiograph has not cleared com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
4

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(45 citation statements)
references
References 9 publications
1
40
0
4
Order By: Relevance
“…If HMD and lung cancer are caused by alveolar deposition of respirable-size particles that contain cobalt associated with tungsten, then our air monitoring exposure data may help to understand lung cancer and explain why HMD is observed among workers exposed to pre-sintered material alone (Meyer-Bisch et al, 1989), post-sintered CTC material alone (Sprince et al, 1988), and both pre-and post-sintered materials (Bech et al, 1962;Coates and Watson, 1971;Sjo¨gren et al, 1980;Davison et al, 1983;Sprince et al, 1984;Cugell et al, 1990;Figueroa et al, 1992;Fischbein et al, 1992). Consistent with these studies, we observed that workers were co-exposed to respirable cobalt-and tungstencontaining particles in all work areas (see Tables 4 and 5) spanning powder production (pre-sintered materials) through handling final product parts (post-sintered materials).…”
Section: Hard Metal Disease and Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…If HMD and lung cancer are caused by alveolar deposition of respirable-size particles that contain cobalt associated with tungsten, then our air monitoring exposure data may help to understand lung cancer and explain why HMD is observed among workers exposed to pre-sintered material alone (Meyer-Bisch et al, 1989), post-sintered CTC material alone (Sprince et al, 1988), and both pre-and post-sintered materials (Bech et al, 1962;Coates and Watson, 1971;Sjo¨gren et al, 1980;Davison et al, 1983;Sprince et al, 1984;Cugell et al, 1990;Figueroa et al, 1992;Fischbein et al, 1992). Consistent with these studies, we observed that workers were co-exposed to respirable cobalt-and tungstencontaining particles in all work areas (see Tables 4 and 5) spanning powder production (pre-sintered materials) through handling final product parts (post-sintered materials).…”
Section: Hard Metal Disease and Lung Cancermentioning
confidence: 99%
“…Workplace studies have identified cases of occupational asthma among CTC workers exposed to both cobalt and tungsten (Davison et al, 1983;Sprince et al 1988;Meyer-Bisch et al, 1989;Shirakawa et al, 1989;Kusaka et al, 1996) and diamond polishers exposed to cobalt alone (Gheysens et al, 1985). Cases of HMD have been reported among workers in all phases of CTC production (Bech et al, 1962;Coates and Watson, 1971;Sjo¨gren et al, 1980;Davison et al, 1983;Sprince et al, 1984Sprince et al, , 1988Meyer-Bisch et al, 1989;Cugell et al, 1990;Figueroa et al, 1992;Fischbein et al, 1992), which may be due to exposures to tungsten carbide particles in association with cobalt particles (Lasfargues et al, 1992(Lasfargues et al, , 1995Lison and Lauwerys, 1990, 1994, 1995Lison et al, , 1996. In humans, excess lung cancer has been observed among hard metal workers exposed to CTC dusts (Lasfargues et al, 1994;Moulin et al, 1998;Wild et al, 2000;Lison et al, 2001), but not among cobalt production workers exposed to cobalt alone (Moulin et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…However, machinists could have cobalt and chromium exposure from the tungsten carbide machining tools. Studies have found that machining with these tools can potentially leach cobalt and chromium into MWFs [Sjogren et al 1980;Walters et al 2012], which can be inhaled via MWF mist or contacted through skin contamination. Our results for cobalt and chromium in used MWF samples were consistent with this finding.…”
Section: Discussionmentioning
confidence: 99%
“…OELs for titanium dioxide exist, but this compound has properties and effects that differ from titanium metal and is beyond the scope of this evaluation. Cobalt exposure has been associated with the development of occupational asthma, pneumoconiosis (a restrictive lung disease caused from inhaling dust), heart problems, and allergic contact dermatitis [Sjogren et al 1980;Gheysens et al 1985;Walters et al 2012]. Some studies have shown that low levels of cobalt can lead to a decrease in lung function [Rehfisch et al 2015].…”
Section: Appendix A: Tablesmentioning
confidence: 99%
“…Cobalt in metalworking fluid may have a greater toxicity than cobalt in the form of a dry powder. Cobalt levels in metalworking fluid can increase to 200 μg/g (approximately 200 mg/L) in some MWFs within the first few weeks of use [Sjögren et al 1980].…”
Section: Recommendationsmentioning
confidence: 99%